Integrating thermal and mechanical characteristics of historic masonry categories: development of a Sicilian database. Issue 1 (October 2021) - Genova, Enrico; La Gennusa, Maria; La Placa, Erica; Vinci, Calogero
Abstract: Detailed construction analysis is essential to the compatible energy improvement of historic buildings. In-situ measurements are crucial for energy diagnosis but their use is limited, especially in vernacular architecture. This paper exposes the development of a hygrothermal and mechanical database for Sicilian historic walls. The proposed method, applied to eleven historic centres, is based on the investigation of those masonry construction features, which recur in local contexts. Preliminary results concern the case study of Petralia Sottana, where a first set of laboratory measurements of stone compressive strength and thermal conductivity was conducted, together with in-situ tests of masonry thermal conductance. Focused on stone walls, these results are used to discuss potentialities and limits of the proposed categorisation of traditional masonry as a support to the energy diagnosis of historic buildings.